Automedicación familiar, un problema de salud pública (2017)
ABSTRACT: Self medicating involves understanding subjectivities that influence the use of medicines. This, leads to the inevitability of comprehensive training for students and professionals in the biomedical sciences, focused on a human and drug-safety perspective. This is an essential tool for the prevention of a public health problem. Objective: To determine the reasons for self-medication in families. Methods: A descriptive cross-sectional case study was conducted between March and August 2013. Information was collected using a questionnaire completed by 51 families. An analysis was performed with 95% confidence intervals and an error of 1.9% using the Epidat 3.1 statistics program. Results: Self-medication without prescription was chosen by 42% of families due to the influence of the media (primarily television), as well as its therapeutic effect. The medicines most frequently used were for common diseases such as influenza, which occurred in 37.25% of adults, 19.61% of children, and 5.88% of elderly family members. The second most common (50.98%) was for hypertension. The highest incidence was by adults (27. 45%) and by the elderly (19.61%). Another use of iterative of medicines is against migraine (39.22%). Discussion: It is evident that there are subjectivities in the chain of use of medicines, with no regard to the risk of affecting public health. Therefore, the challenge of renewing teaching comprehensive training in biomedicine, should be according to socio-cultural educational typology of the professional, student and patient. Thereby allowing the dialogue of knowledge in the decision to use or not to use a particular medicine.